Ecologia populacional de Talitroides topitotum (Burt 1934) (Crustacea, Amphipoda, Talitridae) na região central do Rio Grande do Sul - Brisotto, Gláucia (2022)
Talitroides topitotum is a terrestrial talitrid belonging to the order Amphipoda, which lives in the forest leaf litter, measuring between five and 15 mm. Its occurrence, distribution, and density in the terrestrial environment are related to abiotic parameters, such as air and soil humidity, precipitation, temperature, substrate quality, etc. This group has been little studied in terms of population ecology, both in Brasil and globally, with a few pieces of research about it. T. topitotum was introduced in Brasil in 1972 through garden activities and silviculture. Since then, its impact on the diversity of other species living in leaf litter is unknown. Research about the primary biology of T. topitotum can serve as a basis for future studies. Therefore, we studied the population ecology of T. topitotum in Southern Brasil, considering the population structure and space-temporal distribution. We collected specimens monthly using pitfall traps in São Marcos, Santa Maria/ RS, Brasil, from June/2020 to May/2021. Analysis of environmental factors (temperature, precipitation, and air humidity) was made using the National Institute of Meteorology data. Soil properties (moisture, granulometry and organic matter content) were analyzed in the laboratory. We collected 492 individuals: 62 ovigerous females, 188 females, and 242 juveniles. We did not find males. In chapter one, we discussed the population structure and the relationship between morphometric parameters of T. topitotum with reproductive aspects. Furthermore, we analyzed the latitudinal gradient influence on the body size under the Bergmann effect, comparing our results with other population studies developed in different world regions. We found a relationship between the morphometric parameters body and cephalic length and body and marsupium length. However, we did not find an association between marsupium length and fecundity (number and size of eggs). Although not significant, there was a positive correlation between body size and latitude (p > 0,05). In chapter two, we analyzed the seasonal and spatial distribution of T. topitotum, using the same population, correlating to abiotic factors (moisture, granulometry, and organic matter content) collected in the site of occurrence of the species. The population peak was registered in spring, although the recruitment period was in autumn. The parameters that influenced the seasonal distribution were precipitation and soil moisture. The spatial distribution was assembled in winter, spring and summer and was uniform in autumn. The insertion of new members in the population (recruitment) may explain this fact. We have three hypotheses that can be tested to explain the male absence in this study: i) Wolbachia infection, atrophying secondary sexual characters; ii) presence of asexual reproduction (parthenogenesis) or iii) behaviour differences between males and females, inducing absence of male in the pitfall traps. In the future, more studies will be done to test these hypotheses.